Deletion 16p13.11 uncovers NDE1 mutations on the non‐deleted homolog and extends the spectrum of severe microcephaly to include fetal brain disruption - Alex R. Paciorkowski; Kim M. Keppler‐Noreuil; Luther K. Robinson; Christopher T. Sullivan; Samin A. Sajan; Susan L. Christian; Polina Bukshpun; Stacy Gabriel; Joseph G. Gleeson; Elliott H. Sherr; William B. Dobyns (2013)
Deletions of 16p13.11 have been associated with a variety of phenotypes, and have also been found in normal individuals. We report on two unrelated patients with severe microcephaly, agenesis of the corpus callosum, scalp rugae, and a fetal brain disruption (FBD)-like phenotype with inherited deletions of 16p13.11. The first patient was subsequently found on whole exome sequencing to have a nonsense mutation (p.R44X) in NDE1 on the non-deleted chromosome 16 homolog. We then undertook copy number studies of 16p13.11 and sequencing of NDE1 in nine additional patients with a similar severe microcephaly, agenesis of the corpus callosum, and FBD-like phenotype. The second patient was found to have an inherited deletion of the entire NDE1 gene combined with a frameshift mutation (c.1020-1021het_delGA) in the non-deleted NDE1. These observations broaden the phenotype seen in NDE1-related microcephaly to include FBD. These data also represent the second described syndrome, after Bernard-Soulier syndrome, where an autosomal recessive condition combines an inherited segmental duplication mediated deletion with a mutation in a gene within the non-deleted homolog. Finally, we performed informatics analysis of the 16p13.11 gene content, and found that there are many genes within the region with evidence for role(s) in brain development. Sequencing of other candidate genes in this region in patients with deletion 16p13.11 and more severe neurophenotypes may be warranted.